Arctic Protected Areas; Indicator Report, 2017 - Protection of the Arctic Marine Environment (PAME); Conservation of Arctic Flora and Fauna (CAFF); Guðmundsdóttir, Soffía; Barry, Tom; Helgason, Hólmgrímur (Conservation of Arctic Flora and Fauna / Protection of the Arctic Marine Environment, 2017)
This Arctic Protected Areas Indicator Report, is part of the process that responds to actions identified in both the Framework for a Pan-Arctic Network of Marine protected Areas (PAME 2015) and Actions for Biodiversity, 2013-2021: implementing the recommendations of the arctic Biodiversity Assessment (CAFF 2015). CAFF and PAME Working Groups of the Arctic Council developed this indicator report. It provides an overview of the status and trends of protected areas in the Arctic.